2015
DOI: 10.2460/javma.246.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Reference values, intertest correlations, and test-retest repeatability of selected tear film tests in healthy cats

Abstract: Objective—To determine reference values, intertest correlations, and test-retest repeatability of Schirmer tear test 1 (STT-1), phenol red thread test (PRTT), tear film breakup time (TFBUT), tear osmolarity, and meibometry in healthy cats. Design—Evaluation study. Animals—135 healthy domestic cats aged 0.5 to 12.8 years. Procedures—Each test was performed once in 120 cats and repeated in 40. Pearson correlation was used to assess correlation among tests. Intraclass correlation coefficients (ICCs) and 95% limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
8

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(108 citation statements)
references
References 58 publications
11
89
8
Order By: Relevance
“…This value showed that the STT had poor repeatability in cats (Table ). Although this range was approximately half the previously reported values, it is still a large variation for STT‐1 values (10.4 mm/min). Despite this fact, STT is the most common and conventional method for evaluation of aqueous portion of tear film and should be interpreted in combination with clinical signs in cats…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…This value showed that the STT had poor repeatability in cats (Table ). Although this range was approximately half the previously reported values, it is still a large variation for STT‐1 values (10.4 mm/min). Despite this fact, STT is the most common and conventional method for evaluation of aqueous portion of tear film and should be interpreted in combination with clinical signs in cats…”
Section: Discussioncontrasting
confidence: 48%
“…In the present study, ICC also showed poor test reliability (values <0.40) . Higher ICC values and narrower range of 95% LOA suggest good reliability of a test . The maximum and minimum ranges for 95% LOA were −0.5 to 9.9 mm/min (10.4 mm/min) and 3.3 to 5.3 mm/min (2 mm/min), respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…for dogs, cats, and horses, with differences attributed to microcomponents of the tear film. 14,[31][32][33] Osmolarity in the human volunteers…”
Section: Descriptions Of Tear Osmolarity Have Previously Been Reportedmentioning
confidence: 99%